Diagnóstico del consumo de carne de monte en la comunidad nativa de Remanso, cuenca baja del Putumayo, Loreto, Perú - Chung López, Bettsy Thalya (2022)
The study was carried out in the management area of the Nativa Remanso community, area of influence of the Special Binational Project for Integral Development of the Putumayo River Basin-PEBDICP, located in the district of Yaguas, province of Putumayo, department of Loreto. The objective was to determine the consumption of bushmeat by the inhabitants of the community. For this, a survey was applied to 52 families; each family has an average of 3 individuals, with the average age of the head of the family being 45 years. They prefer in their diet species of wildlife such as Tayassu pecari (75.00%), Agouti paca (61.54%), Pecari tajacu (46.15%), Tapirus terrestris (46.15%), Mazama americana (36 54%), Lagothrix lagotricha (26.92%), Dasyprocta fuliginosa (23.08%), Dasypus novemcintus (23.08%) and Alouatta seniculus (13.46%). 50.0% of the inhabitants indicate that they consume fish 7 times a week; 71.15% of the families of the native community of Remanso, consume bush meat 2 times a week; 69.23 5% of families consume poultry once a month. The average consumption of animal protein is 365.39 gr/day/person. Diagnosis of daily consumption of bushmeat on average is 77.54 gr/day/person, fish is 270.89 gr/day/person and poultry is 16.96 gr/day/ person. The diagnosis of bushmeat consumption in the native community of Remanso is 14.2676 kg/day, 99.8715 kg/week, 428.0208 kg/month, and 5,136.2496 kg/year. The species recorded during the study show that more males (63%) than females (37%) were hunted. The sale price per kg of bushmeat of any species in the native community of Remanso is S/. 5.00 and his main hunting tool is the shotgun.